Modulating the coordination environment of cobalt porphyrins for enhanced electrochemical nitrite reduction to ammonia - Jingwei Han; Hai Sun; Fengkun Tian; Wenwen Zhang; Zonghang Zhang; Ping She; Jun‐Sheng Qin; Heng Rao (Carbon Energy)
Abstract Electrocatalytic reduction of nitrate pollutants to produce ammonia offers an effective approach to realizing the artificial nitrogen cycle and replacing the energy‐intensive Haber‐Bosch process. Nitrite is an important intermediate product in the reduction of nitrate to ammonia. Therefore, the mechanism of converting nitrite into ammonia warrants further investigation. Molecular cobalt catalysts are regarded as promising for nitrite reduction reactions (NO2−RR). However, designing and controlling the coordination environment of molecular catalysts is crucial for studying the mechanism of NO2−RR and catalyst design. Herein, we develop a molecular platform of cobalt porphyrin with three coordination microenvironments (Co‐N3X1, X = N, O, S). Electrochemical experiments demonstrate that cobalt porphyrin with O coordination (CoOTPP) exhibits the lowest onset potential and the highest activity for NO2−RR in ammonia production. Under neutral, non‐buffered conditions over a wide potential range (−1.0 to −1.5 V versus AgCl/Ag), the Faradaic efficiency of nearly 90% for ammonia was achieved and reached 94.5% at −1.4 V versus AgCl/Ag, with an ammonia yield of 6,498 μg h−1 and a turnover number of 22,869 at −1.5 V versus AgCl/Ag. In situ characterization and density functional theory calculations reveal that modulating the coordination environment alters the electron transfer mode of the cobalt active center and the charge redistribution caused by the break of the ligand field. Therefore, this results in enhanced electrochemical activity for NO2−RR in ammonia production. This study provides valuable guidance for designing adjustments to the coordination environment of molecular catalysts to enhance catalytic activity.